2008
DOI: 10.1182/blood-2007-08-109934
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of angiogenesis by ω-3 polyunsaturated fatty acids is mediated by cyclooxygenases

Abstract: The potential role of dietary fats in cancer is attracting considerable interest within the community. Both epidemiologic and experimental findings suggest that omega-3 polyunsaturated fatty acids (-3 PUFAs), which are almost absent from typical Western diets, exert protective effects against cancer progression, although the precise mechanism of this suppression remains unknown. One of the potential targets for -3 PUFAs in cancer suppression is angiogenesis, a process of new blood vessel formation within rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 40 publications
3
81
0
1
Order By: Relevance
“…In addition, other studies have reported that inhibition of either cPLA 2 or iPLA 2 prevents VEGF-induced EC proliferation, supporting a role for these PLA 2 in the modulation of angiogenesis (24,25). Moreover, the observations that whereas feeding mice a -3 PUFA-rich diet reduces angiogenesis, a -6 PUFA-rich diet enhances angiogenesis reinforce a role for PLA 2 in the regulation of angiogenesis (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, other studies have reported that inhibition of either cPLA 2 or iPLA 2 prevents VEGF-induced EC proliferation, supporting a role for these PLA 2 in the modulation of angiogenesis (24,25). Moreover, the observations that whereas feeding mice a -3 PUFA-rich diet reduces angiogenesis, a -6 PUFA-rich diet enhances angiogenesis reinforce a role for PLA 2 in the regulation of angiogenesis (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Tube Formation Require cPLA 2 -mediated AA Release-Recent studies have suggested that PUFA such as AA play a role in the regulation of angiogenesis (27,28). Because cPLA 2 hydrolyzes glycerophospholipids with AA at the sn-2 position, we hypothesized that cPLA 2 -dependent AA release is required for pathological retinal angiogenesis.…”
Section: Vegf-induced Hrmvec Dna Synthesis Migration Andmentioning
confidence: 99%
See 1 more Smart Citation
“…A widely accepted theory to explain the health-promoting effects of omega-3 fatty acids is that they suppress the metabolism of omega-6 arachidonic acid (ARA) to form proangiogenic or proinflammatory eicosanoids or serve as alternative substrates to generate omega-3 lipid mediators with beneficial actions (9). Indeed, the metabolism of omega-3 fatty acids by cyclooxygenase (COX) and lipoxygenase (LOX) enzymes generates 3-series prostaglandins (10,11) and leukotrienes (12), as well as unique omega-3 autacoids such as resolvins and protectins (13), which have antiinflammatory or antiangiogenic effects.…”
mentioning
confidence: 99%
“…Such process is producing three isoforms (VEGFA120, VEGFA164, and VEGFA188) all of them physiologically active. VEGF-A family binds to two tyrosine-kinase receptors: VEGF receptor 1 (VEGFR-1 also known as flt-1) and VEGF receptor 2 (VEGFR-2, also called KDR/Flk-1), which are expressed almost exclusively in endothelial cells (22,23). VEGF-A has been shown to be the necessary factor in angiogenesis induction.…”
Section: Regulation Of Angiogenesismentioning
confidence: 99%